Drugs uses and abuses - Furris, Nicholas J.; Furris, Nicholas J. (Charleston, WV : Cambridge Educational, 2001)
This video describes PCP and evaluates phencyclidine and the veterinary anesthetic ketamine.
tape 1. Narcotics - tape 2. Stimulants - tape 3. Psychedelics and hallucinogens - tape 4. Inhalants - tape 5. Sedatives - tape 6. THC - tape 7. PCP and ketamine - tape 8. Steroids.
Editors : Chris Beavers, Stuart Neal, George Pofantis ; graphics : Keith Kimmell ; executive producer : Charlotte Angel ; production manager : Pamela Trost.
Narrator,Lisa Valdinni.
Keywords: Drug abuse; Subtance abuse; Drugs -- Physiological effect